Peran Dinas Sosial Kabupaten Lingga Dalam Memberikan Bantuan Kepada Penyandang Disabilitas - Zalina Pitri; Tiara . (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
This study examines how the social services of lingga regency assist people with disabilities through social rehabilitation programs and the provision of assistive devices such as wheelchairs, canes, antidecubitus mattresses, and hearing aids. To understand the process of providing assistance and the types of support given, this study uses a descriptive qualitative approach by collecting data from news, official documents, regulations, and interviews with relevant parties. The study shows that the social services regularly distribute hundreds of assistive devices to almost all sub-disrticts in lingga regency and collaborate with various groups to improve the mobility, independence, and quality of life of people with disabilities. To make people with disabilities more empowered socially and economically, the social services promote inclusive policies, cooperate with village govemments and private parties, and provide skills training in addition to physical assistance. This study concludes that the role of the social services agency is quite significant in assisting the social integration of people with disabilities, but there is still a need to strengthen empowerment programs and expand access to services in the future.